Synthesis and characterization of ZnSe1-xTex thin films. (4th May 2021) - Yadav, Brijesh Kumar; Singh, Pratima; Yadav, Chandreshvar Prasad; Pandey, Dharmendra Kumar
ABSTRACT: The present work includes the synthesis of zinc selenium telluride ZnSe1-x Tex (0 ≤ x ≤ 1) ternary compound and its deposition in the form of thin films having thickness 200nm using thermal evaporation technique under high vacuum. The synthesized material ZnSe1-x Tex thin films are characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), UV-VIS-NIR, and Raman spectroscopic measurements. The structural measurements reveal that the deposited thin films of ZnSe1-x Tex material are polycrystalline, whose crystallinity decreases with concentration of tellurium material in thin films. The morphology measurement of films shows that the surface of films is smooth and particles are approximately spherical. The optical band gap estimated from the optical transmission spectra of the films is found to decrease with tellurium concentration. Peak shift is found towards red region with tellurium concentration in the films in Raman spectroscopic measurements. The obtained results are analyzed for application of ZnSe1-x Tex thin films.